Estrategias significativas para resolver problemas multiplicativos en tercer grado de Educación Primaria – 2020 - Chinchayhuara Pineda, Faustino (2021)
The present work of professional sufficiency entitled "Significant strategies to solve multiplicative problems in third grade of Primary Education 2020" had as a fundamental objective to determine the significant strategies applied to solve multiplicative problems of third grade students of Primary Education of Educational Institution No. 0745 Villa Hermosa, district of Uchiza, province of Tocache. These strategies are based on David Ausubel's significant learning theory, Vigostki's sociocultural theory, Johnson & Johnson's cooperative learning and others, adapted and contextualized according to the characteristics of the sample and using the pedagogical and didactic processes of the mathematics area. . The applied strategies were put into practice for a period of ten months, obtaining positive results to share with the rest of the teachers, thus strengthening the achievement of specific competence in this area.